STIPMA (CHILDREN FEEDING INFORMATION STICKS) EDUCATIONAL MEDIA INCREASING MOM'S KNOWLEDGE AND PMBA PATTERNS FOR CHILDREN AGED 6 – 24 MONTHS) - Dewi Praya Untari; Dahliansyah Dahliansyah; Yanuarti Petrika; Desi Desi; Suaebah Suaebah (GEMA KESEHATAN, 2022)
Food intake was influenced by eating patterns in toddlers. If the diet was not achieved properly, it will have an impact on the growth of toddlers. One of the factors that influenced mothers in feeding toddlers was knowledge. STIPMA media was a visual education media modified from flashcard media. The purpose of the study was to analyze the effect of giving STIPMA educational media (child feeding information sticks), the flipcharts Breastmilk Complementary Food Control Card (KUKOMPAS) on mother's knowledge and feeding patterns for toddlers aged 6-24 months at the Kampung Bangka Health Centre. The research was quasi-experimental with a pretest-posttest with a control group design, the research sample was 16 in the control and the other 16 in the treatment group in the Bansir Laut sub-district which was determined based on the inclusion criteria. The treatment was in the form of giving media information sticks and providing education with flipcharts which were carried out for 4 meetings in 21 days. Data analysis used the Wilcoxon rank test, paired t-test, and Independent-test. There was a significant difference in mother's knowledge in the treatment and the control group by giving STIPMA media with a p-value of 0.045<0.05, and there was a difference in feeding patterns of toddlers in the treatment and the control group by giving STIPMA media with a p-value of 0.006>0.05 where the treatment group was better than the control group. The Giving STIPMA media and education using flipcharts could help increase mothers’ knowledge and assist mothers in changing feeding patterns for toddlers. Keywords: Flipcharts, Nutritional Knowledge, STIPMA Media, Toddler feeding pattern